2004
DOI: 10.1083/jcb.200312012
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendroglial modulation of fast axonal transport in a mouse model of hereditary spastic paraplegia

Abstract: Oligodendrocytes are critical for the development of the plasma membrane and cytoskeleton of the axon. In this paper, we show that fast axonal transport is also dependent on the oligodendrocyte. Using a mouse model of hereditary spastic paraplegia type 2 due to a null mutation of the myelin Plp gene, we find a progressive impairment in fast retrograde and anterograde transport. Increased levels of retrograde motor protein subunits are associated with accumulation of membranous organelles distal to nodal comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
276
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 293 publications
(302 citation statements)
references
References 52 publications
23
276
3
Order By: Relevance
“…Aberrant transport and accumulation of organelles in the PNP region is a frequent accompaniment of myelin protein mutations (Salzer, 2003), being reported, for example, in mice with mutations of PLP or CNPase (Lappe-Siefke et al, 2003;Edgar et al, 2004). However, a striking finding in the Caspr mutant mice is that mitochondria accumulate in the nodal region out of proportion to other membranous organelles.…”
Section: Potential Mechanisms Of Nmv Formationmentioning
confidence: 84%
“…Aberrant transport and accumulation of organelles in the PNP region is a frequent accompaniment of myelin protein mutations (Salzer, 2003), being reported, for example, in mice with mutations of PLP or CNPase (Lappe-Siefke et al, 2003;Edgar et al, 2004). However, a striking finding in the Caspr mutant mice is that mitochondria accumulate in the nodal region out of proportion to other membranous organelles.…”
Section: Potential Mechanisms Of Nmv Formationmentioning
confidence: 84%
“…32 It is also known that interactions between oligodendrocytes and neurons influence the activity and health of neurons. 33 Studies have suggested that neurons become vulnerable to cell death in the absence of oligodendrocytes. 34,35 However, the interrelationship between neuronal dysfunction and demyelination are not completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…The relative number of NG2 cells varies in different types of MS lesion in different reports [30][31][32][33][34][35][36] .…”
Section: Remyelination In Multiple Sclerosis (Ms): Ng2 Cells Functionmentioning
confidence: 99%